Hubungan Karakteristik Ibu Primigravida Dengan Komunikasi Terapeutik Terhadap Tingkat Kecemasan Di Puskesmas Andalas Padang - Rizawati (Jurnal Amanah Kesehatan, 2024)
The efficiency of information dissemination through communication will make information dissemination more efficient. Therefore, midwives are expected to be able to provide more effective IEC (Educational Information Communication) to prenatal mothers so that they no longer feel uncomfortable facing the birthing process. The research design used was analytical survey research with a cross sectional study approach, aiming to determine the relationship between the characteristics of primigravida mothers and therapeutic communication on anxiety levels at the Andalas Health Center in 2023. The number of samples in this study was 30 people. With total sampling technique. The data collection instrument was a questionnaire which was used to obtain chi square data. The results of this study show that there is a significant relationship between maternal age and anxiety in pregnant women. There is no significant relationship between maternal education and anxiety among pregnant women. It is hoped that health workers will provide IEC to every pregnant woman at every visit during a pregnancy check regarding the progress of her pregnancy. Keywords: Characteristics; Therapeutic Communication; Anxiety Level